Clinical presentation and management of mycetoma in gezira mycetoma center in Sudan - Ahmed, Moiez M. Aboudi; Alshiekh, Ahmad Alamin; Awadalla, Mohammed D.; Alawad, Awad Ali M. (International Journal of Medicine, 2017)
Background: Mycetoma is a neglected tropical disease characterised by deformity and disabilities with various medical, health, and socioeconomic impacts on the affected communities. It is a common health problem in Gezira state in Sudan.Objective: This study was conducted to review the clinical presentation and management of mycetoma in Gezira Mycetoma Center in Medani, Sudan.Methodology: This was a prospective descriptive health facility-based study conducted among 100 patients diagnosed with mycetoma attended to Gezira Mycetoma Center during the period from October 2014 to Sept. 2015. Variable checked was demographic characteristic, clinical presentation, types of mycetoma, and types of surgery done.Results: The commonest age was 20-40 years, which represents 49(49%). Males were 76(76%). Participants were mostly farmers or animal breeders with percentage of 31% and 12% respectively. All patients presented with a swelling (100%) and mostly with discharge in a sinuses (75%).The vast majority of patients reside in Gezira State (82%). Eumycetoma was reported in 98% of cases versus 2% actinomycetoma. Diagnosis depended on clinical examination mainly and X-ray for bone involvement which was reported in 15%. All cases underwent surgical intervention in the form of wide local excision (81%), amputation (17%) and debulking (2%).Conclusion: The study concluded that most of the patients presented late, with history of inadequate management.